Emergence of acute/subacute infant-juvenile paracoccidioidomycosis in Northeast Argentina : effect of climatic and anthropogenic changes? - Giusiano, Gustavo Emilio (2019)
Fil: Giusiano, Gustavo Emilio. Universidad Nacional del Nordeste. Instituto de Medicina Regional; Argentina.